MANAGEMENT OF CAREER DEVELOPMENT OF ISLAMIC CHAPLAINS TNI IN SUPPORTING SOLDIERS' OPERATIONAL READINESS AT THE HEADQUARTERS OF THE INDONESIA NATIONAL ARMY - Muttaqin, Muttaqin; Chusnan, Masyitoh; Uksan, Arifuddin (Ridwan Institute, 2024)
This research is driven by the Sendai Framework, which serves as a guide for mitigating global disaster risk. Within the ASEAN context, this framework is encapsulated in the form of a collective agreement among ten countries. AADMER serves as the foundation for ASEAN member states to establish and enhance coordination and collaboration in the field of disaster management. This research examines how the AHA Centre effectively communicates and disseminates the regional disaster management mechanisms to National Disaster Management Organisations in the Philippines and Malaysia through the One ASEAN One Response Roadshow programme, and how one country’s approaches are different from another by considering certain local contexts. This study explores the critical factors contributing to the success of these communication efforts and highlights the importance of intercultural communication in enhancing understanding and collaboration among stakeholders in each country. The findings reveal that effective communication strategies are vital for fostering mutual understanding and cooperation, thereby strengthening regional disaster management capacities. This research contributes to both academic and practical domains by offering insights into successful strategies for disseminating disaster management information in a multi-cultural and multi-sectoral regional context.